1970
DOI: 10.1128/iai.1.6.559-565.1970
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Vaccines in Experimental Mycoplasma pneumoniae Disease

Abstract: The mechanisms of immunity to Mycoplasma pneumoniae were investigated by evaluating different vaccination procedures in an experimental animal model. Hamsters were immunized by intranasal inoculation of broth cultures or by parenteral injections of saline-suspended organisms. All vaccinees received a standardized intranasal challenge which produced pneumonia in 94% of controls. Intranasal immunization with virulent organisms produced a 71 % reduction in pneumonia. Subcutaneous and intraperitoneal inoculation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
37
0

Year Published

1972
1972
2009
2009

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 12 publications
4
37
0
Order By: Relevance
“…Hamsters with a high serum antibody level produced by parenteral administration of killed M. pneumoniae vaccine did not show resistance to the experimental inoculation of M. pneumoniae (5), while animals previously infected with the organisms had a low serum antibody level but were resistant to reinfection (5)(6)(7). Hence those authors concluded that there was little correlation between serum antibody titer and protection against M. pneumoniae pneumonia in vaccinated hamsters.…”
Section: Discussionmentioning
confidence: 99%
“…Hamsters with a high serum antibody level produced by parenteral administration of killed M. pneumoniae vaccine did not show resistance to the experimental inoculation of M. pneumoniae (5), while animals previously infected with the organisms had a low serum antibody level but were resistant to reinfection (5)(6)(7). Hence those authors concluded that there was little correlation between serum antibody titer and protection against M. pneumoniae pneumonia in vaccinated hamsters.…”
Section: Discussionmentioning
confidence: 99%
“…One is that INF-a induced by mycoplasma-contamination in target cells might be responsible for enhancement of cytotoxic activity of macrophages and NK cells. The other is that TNF-a induced by pathogeneic mycoplasmas in human and animal, may play a role in resistance to mycoplasma infections in riz'o, through enhancement of cellular immune response (3,6) which might be responsible for protection of mycoplasma infection rather than humoral immunity in these mycoplasma infections (12). There have been several reports that mycoplasmas enhance the cytotoxic activity of macrophages and NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…hamsters previously infected with M. pneumoniae were found to be more resistant to pneumonia upon reinfection, even if they had low serum antibody titers (10,12,16). However, in our previous investigations, resistance to M. pneumoniae infection in hamsters corresponded to serum antibody titers in animals actively immunized with adjuvant vaccine (17) or adoptively immunized with serum preparations (17,18).…”
mentioning
confidence: 70%
“…M. pneumoniae pneumonia responds satisfactorily to the appropriate antibiotics, but the organisms are not effectively eradicated from the respiratory tract (14,23). Efforts have been directed toward the development of a vaccine for prophylaxis (7,10,12,17,25).Resistance of humans to M. pneumoniae infection has been reported to be correlated directly with the presence of serum antibodies (7,20,22,28). In hamsters, a high level of serum antibody produced by parenteral vaccination with killed M. pneumoniae was not accompanied by protection (l 0) .…”
mentioning
confidence: 99%
See 1 more Smart Citation